2011
DOI: 10.2174/187221411797265881
|View full text |Cite
|
Sign up to set email alerts
|

Current and Future Development of Estrogen Receptor Ligands: Applications in Estrogen-Related Cancers

Abstract: 17β;-Estradiol (E2), via its cognate receptors (ERs), regulates several aspects of human physiology including development, reproduction and tissue homeostasis. Consequently, E2 could also be implicated in the development or progression of several pathologies, including cancer. Two different ER subtypes are present in mammals (ERβ and ERβ), which display specific roles in E2-related cancers, different tissue distribution, and multiple action mechanisms (i.e., genomic and extranuclear mechanisms). Here, the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 127 publications
(240 reference statements)
0
15
0
Order By: Relevance
“…Membrane ERα expressing breast cancers also show a strong positive correlation with phosphorylated Akt and HER2 overexpression [280], the latter of which is characteristic of ‘invasive carcinoma’ [281]. In addition, ERα plasma membrane localization and its interactions with IGFR1 and EGFR/ErbB2 may be one of the mechanisms underlying the development of drug resistance in breast cancer cells [282,283]. Androgen independent prostate cancer is also mediated by IGFR-1/IGF-1 [284] and elevated EGFR/ErbB-2 [285], combined with downstream Akt [286,287] and Janus kinase (JAK)/STAT [288] and MAPK signaling.…”
Section: The Role Of Estrogen and Androgen Receptors In Cancer Celmentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane ERα expressing breast cancers also show a strong positive correlation with phosphorylated Akt and HER2 overexpression [280], the latter of which is characteristic of ‘invasive carcinoma’ [281]. In addition, ERα plasma membrane localization and its interactions with IGFR1 and EGFR/ErbB2 may be one of the mechanisms underlying the development of drug resistance in breast cancer cells [282,283]. Androgen independent prostate cancer is also mediated by IGFR-1/IGF-1 [284] and elevated EGFR/ErbB-2 [285], combined with downstream Akt [286,287] and Janus kinase (JAK)/STAT [288] and MAPK signaling.…”
Section: The Role Of Estrogen and Androgen Receptors In Cancer Celmentioning
confidence: 99%
“…Nuclear localization of ERs [294,295] is now considered to have prognostic significance. Very few drugs for breast cancer have been shown to target ERs extranuclear mechanisms [283]. …”
Section: The Role Of Estrogen and Androgen Receptors In Cancer Celmentioning
confidence: 99%
See 1 more Smart Citation
“…The extranuclear ER pathway is involved in several crucial cellular functions such as cell proliferation, migration, secretion, and apoptosis [3], [4]. Knowledge on these novel estrogen actions is now significantly broadening our understanding of breast carcinogenesis, particularly regarding metastasis and drug resistance [5], [6].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that activation of ERβ with ERB-041 inhibited UVB-induced skin tumorigenesis by interfering with proinflammatory signaling is consistent with other studies. The mechanism underlying this effect was not definitively shown in this study but could be due to ERβ interfering with NF-κB-dependent signaling as suggested by others (19). This type of interaction has also been noted with other nuclear receptors such as peroxisome proliferator-activated receptors (20).…”
mentioning
confidence: 55%